Genetic improvement, support to aquaculture value chains and promotion of fish in foods systems in the Southern African Development Community (SADC) - Komugisha, Basiita Rose (WorldFish, 2022)
WorldFish Genetics Workshop 2022- presentation on genetic improvement, support to aquaculture value chains and promotion of fish in foods systems in the Southern African Development Community (SADC)